Etnopedagogik: Nilai-Nilai Kearifan Lokal Pada Rampak Genteng Sebagai Sumber Pembelajaran Sosiologi - Dini Miftakhul Jannah Dwi Putri; Dadan Wildan; Siti Komariah (Universitas Pendidikan Indonesia, 2024)
This research explores the cultural phenomenon of the Ceramic Music Festival (Rampak Genteng) in Jatiwangi, Majalengka, focusing on its integration into sociology education. The festival, initiated by the Jatiwangi Art Factory community, celebrates local wisdom through music created from clay, emphasizing the community's longstanding expertise in tile-making. The study employs qualitative field research, utilizing interviews and literature review as data collection methods. It investigates how the festival embodies local wisdom, encompassing values such as religiosity, communal solidarity, artistic expression, historical significance, and economic resilience. These values are integral to sociology education, enriching lessons on community empowerment and social harmony. Project-Based Learning (PJBL) serves as a pedagogical approach to integrate these values into the sociology curriculum effectively.